Monitoreo serológico de anticuerpos (IgG e IgM) contra Babesia bigemina (Haemosporidia: Babesiidae) en becerros del trópico mexicano - Solís-Calderón, J J (1998)
Antibody dynamics (IgG and IgM) against Babesia bigemina was studied on 41 under 15 days of age from tbree ranches (Rl , R2 and R3) in Yucatan, Mexico. Blood samples were collected every 30 days, for eight months. Sera were tested by the indirect fluorescent antibody method to detect IgG and IgM. Overall IgM seroprevalence during the calves first eight months of life was 17.i % without relation to age. Overall IgG seroprevalence was 66.8%, increasing with age. Seroprevalence in RI , R2 and R3 were 87.5%, 77.1% and 31.8% respectively. Ranches 1 and 2 were in enzootic stability. In Yucatan, the modification of management factors in ranches with enzootic instability, could increase the risk of clinical babesiosis. Cattle mobilization from ranches with enzootic instability must be strictly controlled.